2002
DOI: 10.1111/j.1755-6686.2002.tb00198.x
|View full text |Cite
|
Sign up to set email alerts
|

Organ donation: Attitude and knowledge of nurses in South Africa

Abstract: Various factors influence the process of organ donation. As a result, there is a shortage of organs for transplant. Poor communication and cooperation between transplant coordinators and intensive care nursing staff can lead to the non-referral of potential organ donors, which is detrimental to the process. The purpose of this research was to ascertain the attitude and knowledge of the transplant coordinators and intensive care nursing staff that work in intensive care units during organ donation. Contextual d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…These data confirm what has already been found in other European countries, where a negative attitude has been reported and where a lot of fear and uncertainty surrounds the topic of organ donation and transplantation. [13][14][15][23][24][25] In fact, when we analyze the studies reporting that nurses are in favor, 16,17,26 we see that most have very low questionnaire completion rates, which could cause a positive bias in the selection of the sample because persons who are in favor tend to be more prepared to complete the questionnaire than persons who are against or undecided, and this fact could explain the high favorable attitude. For example, in the study by Molzahn, 17 92% of nursing respondents are in favor, but the survey completion rate is only 50%.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These data confirm what has already been found in other European countries, where a negative attitude has been reported and where a lot of fear and uncertainty surrounds the topic of organ donation and transplantation. [13][14][15][23][24][25] In fact, when we analyze the studies reporting that nurses are in favor, 16,17,26 we see that most have very low questionnaire completion rates, which could cause a positive bias in the selection of the sample because persons who are in favor tend to be more prepared to complete the questionnaire than persons who are against or undecided, and this fact could explain the high favorable attitude. For example, in the study by Molzahn, 17 92% of nursing respondents are in favor, but the survey completion rate is only 50%.…”
Section: Discussionmentioning
confidence: 95%
“…In this situation, it is a matter of great concern that various studies have shown that organ donation and transplantation generate stress among nurses and that nurses lack information on the topic, [13][14][15][16] although some authors 17 report that nurses have a very favorable attitude.…”
mentioning
confidence: 99%
“…International and SA research have shown that this type of uncertainty can hinder organ donation in a highly pressurised clinical environment where organisational routine and structured interaction are essential for its success. [5,12] Our study revealed that the lack of knowledge about organ donation and uncertainty about policies and roles in organ donation may also be explained by a lack of formal organ donation education for nurses in the Johannesburg region. However, nurses in the private sector scored higher on the knowledge component of the questionnaire compared with those in the state sector.…”
Section: Discussionmentioning
confidence: 89%
“…Again, local studies have confirmed that most trainee/qualified nurses and medical students are in favour of organ donation, and their stance is influenced more by education regarding organ donation than gender, cultural identity or ethnicity. [4][5][6] So why are our organ-donor rates still so frustratingly low? Low donation rates have been the focus of many international transplant communities.…”
Section: In Practicementioning
confidence: 99%